The Economics of Money, Banking and Financial Markets - Mishkin, Frederic S.
The Economics of Money, Banking and Financial Markets / Frederic S Mishkin .- United Kingdom : Pearson Education Limited , 2019 .- 739 p. ; 25cm .- 9781292268859